PENINGKATAN PERAN PEGAWAI WANITA DI LINGKUNGAN PEMERINTAH PROVINSI PALANGKA RAYA MELALUI PELATIHAN DAN PENGEMBANGAN KOMPETENSI - Toendan, Rita Yuanita; Lampe, Normand Armando (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This Community Service activity aims to analyze the importance of training and competency development for female employees within the Palangka Raya Provincial Government. The main focus is directed at the identification of training needs, barriers to self-development, and the effectiveness of need-based training. The methods used included a survey of 40 female employees, in-depth interviews, and the implementation of module-based short training. The results show that the majority of respondents have never received leadership training and that the mastery of digital skills is still limited. After participating in the training, there was an increase in the average competency score of participants by 30%, as well as an increase in confidence and participation in work forums. This training also received a positive response from several agencies that intend to replicate it. These findings show that the development of female employee competencies not only supports organizational effectiveness, but also strengthens efforts towards an inclusive and gender-responsive bureaucracy.